Annotated bird sighting list for summer 1998 compiled by Steve Fairbairn - Fairbairn, Steve E.et al (1998)
An annotated list of birds sighted by Steve Fairbairn. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1998.